The evolution of luminous infrared galaxies through cosmic time - Hogan, L (2022)
(Ultra) Luminous infrared galaxies (U/LIRGs) are amongst the most powerful star forming galaxies in the universe. They play a significant role in galaxy evolution and dominate the star formation rate density at the peak of cosmic star formation, at z ∼ 2. Therefore, understanding the properties of luminous infrared galaxies, and how these properties evolve through cosmic time, is necessary for testing our best theories of galaxy evolution, and for pushing the current understanding of cosmic star formation.